2022
DOI: 10.1007/s12282-022-01389-3
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Trop-2 expression in breast cancer cells by clinically used therapeutic agents and acquired tamoxifen resistance

Abstract: Background Sacituzumab govitecan is an antibody–drug conjugate that delivers SN-38, an active metabolite of irinotecan, to the target molecule, trophoblast cell-surface antigen 2 (Trop-2). It is a promising drug for triple-negative breast cancer and is anticipated to be effective for luminal breast cancer. The efficacy of the agent relies on the expression of Trop-2 rather than its intracellular function. However, conditions that alter the Trop-2 expression have not been well investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…The two known resistance mechanisms are AKT activation and Notch signaling. A third possible mechanism seems to be tamoxifen-induced Trop-2 expression through the transcription factor TFEB [ 56 ]. There are probably also other mechanisms that are not yet known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two known resistance mechanisms are AKT activation and Notch signaling. A third possible mechanism seems to be tamoxifen-induced Trop-2 expression through the transcription factor TFEB [ 56 ]. There are probably also other mechanisms that are not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, chemotherapy can, in some cases, increase Trop-2 expression. For example, tamoxifen treatment significantly increased Trop-2 expression in breast luminal cancer cell lines [ 56 ].…”
Section: Trop-2 and Drug Resistancementioning
confidence: 99%
“…It has also been shown that patients with lower TROP-2 expression have reduced mPFS when treated with sacituzumab govitecan as compared to those with higher expression (2.7 months vs. 6.9 months, respectively) [ 55 ]. Zhu et al, 2022, evaluated how various treatments could alter TROP-2 expression and found that treatment with tamoxifen significantly increased TROP-2 expression [ 56 ].…”
Section: Challenges and Resistance Mechanismsmentioning
confidence: 99%
“…Trophoblast cell surface antigen 2 (Trop2) is a widely expressed glycoprotein and a member of the epithelial cell adhesion molecule (EpCAM) family in many normal tissues, and overexpressed in a variety of human cancers, including gastric cancer [ 98 ] and breast cancer [ 99 ]. Trop2 has potential in promoting epithelial-mesenchymal transition (EMT) in human breast cancer [ 100 ].…”
Section: Car T-cell Therapy In Solid Tumorsmentioning
confidence: 99%